Sharing and seeking information about skin cancer risk and prevention among Hispanic people from Florida and Puerto Rico - Jessica N. Rivera Rivera; John Charles A. Lacson; Youngchul Kim; Richard G. Roetzheim; Steven K. Sutton; Brenda Soto-Torres; Susan T. Vadaparampil; Peter A. Kanetsky (Elsevier, 2023)
Objective: To explore factors associated with communication and information-seeking after receipt of skin cancer prevention information among Hispanic individuals. Methods: Multivariable logistic regression was used to analyze existing data on demographics, personal experience, salience, and beliefs variables collected from Hispanic individuals to determine independent associations with sharing and seeking information about skin cancer prevention. Results: Of 578 participants, 53% reported any communication about skin cancer prevention behaviors or skin cancer genetic risk; and 31% and 21% sought additional information about preventive behaviors or genetic risk, respectively. Female sex, greater perceived severity, higher comparative chance of getting skin cancer, and lower health literacy were associated with greater communication, while having no idea of one's own skin cancer risk was related to less communication. Greater health numeracy and higher cancer worry were associated with information-seeking about prevention behaviors and genetic risk. Conclusion: Up to half of participants reported communication or information-seeking, although factors associated with specific activities differed. Future studies should evaluate how to promote communication behaviors in the Hispanic community and how sharing and seeking information influence an individual's network prevention practices. Innovation: Several factors related to communication behaviors among Hispanic people after obtaining skin cancer prevention information were identified.Trial registration: This trial was registered on clinicaltrials.gov (NCT03509467).